2017
DOI: 10.1007/s10709-017-9983-9
|View full text |Cite
|
Sign up to set email alerts
|

Landscape genetics in the subterranean rodent Ctenomys “chasiquensis” associated with highly disturbed habitats from the southeastern Pampas region, Argentina

Abstract: Studies of genetic differentiation in fragmented environments help us to identify those landscape features that most affect gene flow and dispersal patterns. Particularly, the assessment of the relative significance of intrinsic biological and environmental factors affecting the genetic structure of populations becomes crucial. In this work, we assess the current dispersal patterns and population structure of Ctenomys "chasiquensis", a vulnerable and endemic subterranean rodent distributed on a small area in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…It should be noted that other species of subterranean rodents distributed at similar spatial scales to C. australis, or even smaller, have also revealed the importance of landscape characteristics such as the habitat availability (Sato et al 2014;Kierepka et al 2016;Biello et al 2018;Visser et al 2018). Our results also agreed with those published by Galiano et al (2014) in C. minutus (a species with a linear coastal geographic distribution of 300 km on the southeastern of Brazil) and Mora et al (2017) in C. "chasiquensis" (with a distribution of 100 km in central Argentina) using microsatellite loci. These authors observed that those tuco-tucos distributed in areas with higher habitat availability were associated to greater genetic diversity.…”
Section: Discussionsupporting
confidence: 90%
“…It should be noted that other species of subterranean rodents distributed at similar spatial scales to C. australis, or even smaller, have also revealed the importance of landscape characteristics such as the habitat availability (Sato et al 2014;Kierepka et al 2016;Biello et al 2018;Visser et al 2018). Our results also agreed with those published by Galiano et al (2014) in C. minutus (a species with a linear coastal geographic distribution of 300 km on the southeastern of Brazil) and Mora et al (2017) in C. "chasiquensis" (with a distribution of 100 km in central Argentina) using microsatellite loci. These authors observed that those tuco-tucos distributed in areas with higher habitat availability were associated to greater genetic diversity.…”
Section: Discussionsupporting
confidence: 90%
“…Most landscape genetics inference studies have assumed either a positive or negative linear relationship between landscape features and cost surfaces (Garroway, Bowman, & Wilson, 2011;Koen, Bowman, & Walpole, 2012), including examples with rodent populations (Chiappero et al, 2016;Howell et al, 2017;Mora et al, 2017;Ortiz et al, 2017), despite that nonlinear responses are expected to be more common (Marrotte & Bowman, 2017;. Here, we found nonlinear relationships relative to landscape resistance for both humidity and temperature, variables that influence genetic connectivity in different species like the northern quoll (Dasyurus hallucatus; Hohnen et al, 2016) and Liomys pictus (Garrido-Garduño et al, 2015).…”
Section: Environmental Features and Genetic Connectivitymentioning
confidence: 64%
“…These changes have caused the loss of biodiversity for many native species and the acceleration of habitat fragmentation in the case of tuco-tucos populations ( Tiranti et al, 2005 ; Mora et al, 2017 ; Mapelli et al, 2017 ). The species C. talarum and C. pundti were recently classified as Vulnerable (VU) and Endangered (EN) respectively, with dune afforestation, agriculture, floods and habitat fragmentation as the main triggers ( Fernández et al, 2019 ; Fernández and Carnovale, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results show a high specificity of each group of species in terms of the occupation of different habitats. In particular, soil characteristics could be a good predictor of the occurrence of each species of Ctenomys from different phylogenetic groups (see Mora et al, 2016Mora et al, , 2017 for the nominal form C. "chasiquensis"; see Mapelli et al, 2012Mapelli et al, , 2017 for C. azarae and C. porteousi). Such specificity in occupation of different environment configurations goes beyond geographical proximity, since, in many regions, species of different phylogenetic groups are very close to each other (e.g., Macachín and Guatraché; see Figure 1).…”
Section: Populations Of Mendocinus Groupmentioning
confidence: 99%